Pemberdayaan Masyarakat Melalui Pembuatan Lidi dengan Memanfaatkan Sumber Daya Lokal untuk Meningkatkan Pendapatan di Desa Perkebunan Maryke - Jannatul Ma’wa Manurung; Afifah Fauziyah Sitanggang (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This service activity aims to empower the people of Maryke Plantation Village through making stikcs as a home bussiness that utilizes collected palm tree fronds. Situation analysis shows that this village has abundant local resource potential, but it has not been utilized optimally to increase community income. The main problem faced is the lack of optimization in the process of making sticks and the sales location is limited the only one sales location. The methods used include assitance in the production process and assistance in the distribution of products to village suppliers. The results of this activity show an increase in optimizing local resources to increase village residents’ income. The discussion emphasized that empowerment based on local resources can increase the economic independence of the community and improve overall welfare.